Information System Design And Manufacture Online Booking Car Service Website Based And Spare Part Availability At CV. Bersama Maju Service Central Jakarta Branch - Rahmawati, Dwi; Sharyanto, Sharyanto; Gunawan Sudarsono, Bernadus (Journal of Engineering, Technology and Computing (JETCom), 2023)
CV. Bersama Maju Service is a company engaged in the field of car repair and maintenance services. At CV Bersama Maju Service the registration process for services is still done manually using paper besides that the data is still processed using Microsoft Excel and Microsoft Word so that it takes quite a long time and is considered inefficient, especially for storing the data. And to overcome all these obstacles a study was made entitled "Information System Design And Manufacture Online Booking Car Service Website Based And Spare Part Availability At CV. Together with Maju Service Central Jakarta Branc ”. This study was designed and modeled using the Unifield Modeling Language (UML) and programmed using PHP and using MySQL for the database. With this research is expected to simplify existing processes.